Design and Development of Mobile Application Using Android Studio Software for Learning the Course Research Methodology Effectively - STTPMARM - Dol, Sunita M.; Jawandhiya, P. M. (Journal of Engineering Education Transformations, 2025)
There is a rapid adoption of mobile technology in teaching-learning process of education system. Now a day, the teaching-learning process benefits greatly from the mobile application which makes the learning easy. Students/ learners can go through the contents of the app at their own pace and actively engaged in joyous learning process. Keeping this view in mind, an android mobile application RM (Research Methodology) is developed using Android Studio. This course is important for all students who are doing their graduation, post-graduation and doctorate in any stream such as Engineering, Science, Commerce, Arts, etc. In this research article, new instructional strategy called STTPMARM (Short Term Training Programme using Mobile Application for Research Methodology) is considered for research scholars of university. A Short Term Training Programme (STTP) titled ‘Research Methodology’, and sponsored by ISTE (Indian Society for Technical Education) was organised in the college for research scholars for the course Research Methodology as a part of PhD coursework. PowerPoint presentation for each unit of this course available in this app was used during this STTP and Research Methodology (RM) app was given offline to the research scholar for revising the content covered on the particular day of the STTP. In current study, the contents of this app and students’ perception about this app are provided. Also this app was used on sample of 42 research scholars to check the effectiveness of this app. Test was conducted after each unit content as well as final test covering all units of this course. From the feedback about this mobile app, it is found that 100% students like the concept of using mobile app for learning the course Research Methodology.